Enhancing mentalization by specific interventions within mentalization-based treatment of adolescents with conduct disorder - Kasper, Lea A.; Hauschild, Sophie; Schrauf, Lisa M.; Taubner, Svenja (Frontiers in Psychology, 2024)
Objective: Mentalization is discussed as a mechanism of change in psychotherapy due to its positive effects on psychological functioning. In order to specifically apply mentalization-based interventions, a better understanding of the relationship between interventions and in-session mentalization is needed. The study aimed to explore the association between interventions and effective mentalizing. Method: Fifteen therapy sessions of three therapies with male adolescents with conduct disorder were transcribed and rated with the Reflective Functioning (RF) Scale and a newly developed Mentalization-based Treatment (MBT) intervention coding manual. The coded interventions were categorized into intervention levels according to the MBT manual (Bateman & Fonagy, 2016). Fisher's exact tests were performed to test differences in frequencies of interventions in high-RF sequences (RF score ≥4) compared with remaining therapy sequences (RF score ≤ 3). Results: Specific MBT interventions such as demand questions, affect-elaboration, empathic validation, change of subject, challenge, patient-therapist relation and mentalizing for the patient were related to effective mentalizing. Moreover, intervention levels such as supportive & empathic, basic-mentalizing & affect mode and relational mentalizing were positively associated with effective mentalizing. Conclusion: MBT interventions seem to promote effective mentalizing at various intervention levels. Interventions that enhance effective mentalizing seem to be patient specific. In line with MBT theory, their effect on effective mentalizing might depend on various variables, such as the patients' arousal and pre-mentalizing mode.